Impact of sexual knowledge, attitude, and exposure to pornography on sexual behaviour among urban adolescents in Peninsular Malaysia - Wong, Fui Ping (2012)
Adolescents’ liberal sexual behaviour is becoming a distressing trend for the country, with increasing number of teenage girls getting pregnant and seeking help from welfare department. This study aimed to determine the association between sexual behaviour with its selected contributing factors (sexual knowledge, sexual attitude, exposure to pornography, gender and having a romantic partner). The respondents were 860 adolescents, aged 13 to18 years, from developed urban areas in north (Penang Island), central (Klang Valley) and south (Johor Bahru) of Peninsular Malaysia. Data were gathered through self-administered questionnaire. Statistical analyses employed were descriptive analysis which is Exploratory Data Analysis (EDA) to describe the data, Principle Component Analysis (PCA) to analyze the component of data, and Spearman’s Rho and Path Analysis to test the hypotheses of the study. Approximately 36% of the respondents reported that they engaged in at least one type of sexual behaviour; and 11% of the respondents engaged in sexual intercourse. In general,male respondents and respondents who reported having a romantic partner appeared to be more active in sexual behaviour. Results of the Spearman’Rho correlation indicated that sexual attitude, exposure to pornography, gender and have a romantic partner were significantly associated with sexual behaviour among respondents. The finding of path analysis showed that the model supported the direct relationship between sexual attitude and exposure to pornography with sexual behaviour. The direct relationship between sexual knowledge and sexual behaviour was not supported by the model. The results of the study also indicated that exposure to pornography mediates the relationship between sexual attitude and sexual behaviour. Gender moderates the influence of sexual attitude on sexual behaviour. The influence of sexual attitude on sexual behaviour is stronger for male compared to female respondents. In addition, having a romantic partner did not moderate the relationships between sexual knowledge, sexual attitude, and exposure to pornography with sexual behaviour. The findings of the study highlighted that positive sexual attitude and less exposure to pornography may prevent adolescents from engaging in sexual behaviour especially among male adolescents. Overall, the study contributes to the fundamental understanding of Malaysian adolescents’ development, specifically on sexual development. In addition, the findings of the study also imply the need to encourage positive sexual attitude among respondents. The findings from this study may provide useful information regarding adolescents’sexual behaviour to educators, policy makers, parents and caregivers, counsellors and professionals who work closely with adolescents.